Effectiveness of Blended Learning Web-Based Model in Students’ Listening Skill - Netty Huzniati Andas; Karman Karman; Nyoman Indah Artini (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The purpose of this study was to determine the significant impact of utilizing a Blended Learning Web-Based Model on students' listening skills. The specific quasi-experimental design employed in this study was the Time Series design, which involved a single group and did not require a control group. The research included 28 students from the second semester in a listening class as participants, who received instruction using the blended learning web-based model. For data collection, the researcher administered a listening test at the beginning of the study and after the treatment. The data were analyzed using SPSS version 22. The findings of this research indicated a significant improvement in students' listening skills after implementing the Blended Learning Web-Based Model for teaching listening. It was observed that the average score on the post-test (58.79) was higher than the average score on the pre-tests (43.79). Furthermore, the result of the T-test (3.586) exceeded the critical T-table value (2.052), leading to the acceptance of the alternative hypothesis (H1) and rejection of the null hypothesis (H0).